Identification of key components in the energy metabolism of the hyperthermophilic sulfate-reducing archaeon Archaeoglobus fulgidus by transcriptome analyses - Hocking, William Peter; Stokke, Runar; Roalkvam, Irene; Steen, Ida Helene (Frontiers in Microbiology, 2014)
Energy conservation by the pathway of dissimilatory sulfate reduction is present in a diverse group of prokaryotes, but is most comprehensively studied in Deltaproteobacteria. Herein, whole-genome microarray analyses where used to provide a model of the energy me-tabolism of the sulfate reducing archaeon Archaeoglobus fulgidus, based comparative analysis litoautotrophic growth with H2/CO2 and thiosulfate, and heterotrophic growth on lactate with sulfate or thiosulfate. Only 72 genes were expressed differentially between the cultures utiliz-ing sulfate or thiosulfate whereas 269 genes were affected by a shift in energy source. We identified co-located gene cluster encoding putative lactate dehydrogenases (lldD, dld, lldEFG), also present in sulfate reducing bacteria. These enzymes may take part in energy conservation in A. fulgidus by specifically linking lactate oxidation with APS reduction via the Qmo complex. High transcriptional levels of Fqo confirm an important role of F420H2 and menaquinone mediated electron transport chain during heterotrophic growth. A putative pe-riplasmic thiosulfate reductase was identified by specific up-regulation. Also, putative genes for transport of sulfate and sulfite are discussed. We present a model for hydrogen metabo-lism, based on the probable bifurcation reaction of the Mvh:Hdl hydrogenase, that may inhibit the utilization of Fdred for energy conservation. Rather, energy conservation is probably facili-tated via menaquinone to multiple membrane bound heterodisulfide reductase complexes and the enzyme DsrC – linking periplasmic hydrogenase (Vht) to the cytoplasmic reduction of sulfite. The ambiguous roles of genes corresponding to fatty acid metabolism induced during growth with H2 are discussed. Putative co-assimilation of organic acids is favored over a homologues secondary carbon fixation pathway, although both mechanisms may contribute to conserve the amount of Fdred needed during autotrophic growth with H2.